System Modelling and Optimization 1996
DOI: 10.1007/978-0-387-34897-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic optimization methods in engineering

Abstract: Yield stresses, allowable stresses, moment capacities (plastic moments), external loadings, manufacturing errors are not given fixed quantities in practice, but have to be modelled as random variables with a certain joint probability distribution. Hence, problems from limit (collapse) load analysis or plastic analysis and from plastic and elastic design of structures are treated in the framework of stochastic optimization. Using especially reliabilityoriented optimization methods, the behavioral constraints ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Numerous studies (Catoni and Picard, 2004;Spall, 2004;Cao, 2007;Shukla and Mishra, 2014;Marti, 2015;Williams, 2013;Song, 2013;Bertocchi, Consigli and Michael, 2011) showed that the execution of the work is well described by a beta probability distribution. The expectation (average) time performance can be estimated from the formula: To determine the critical path of the project critical path method is used.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies (Catoni and Picard, 2004;Spall, 2004;Cao, 2007;Shukla and Mishra, 2014;Marti, 2015;Williams, 2013;Song, 2013;Bertocchi, Consigli and Michael, 2011) showed that the execution of the work is well described by a beta probability distribution. The expectation (average) time performance can be estimated from the formula: To determine the critical path of the project critical path method is used.…”
Section: Discussionmentioning
confidence: 99%
“…В зависимости от желания проектировщика и имеющихся возможностей уточнения информации, управления ХТПС во время его эксплуатации, такие задачи принимают различный вид задач стохастической оптимизации [2]. Можно выделить задачи робастной стохастической оптимизации, учитывающие жесткие ограничения [3], и задачи оптимизации с мягкими ограничениями, которые чаще всего представляют в форме вероятностных ограничений [4]. При этом соблюдается весьма высокий уровень выполнения таких ограничений, или малый уровень риска.…”
Section: Introductionunclassified